ISO-standardized smart city platform architecture and dashboard - Zdraveski, Vladimir; Kocarev, Ljupco; Trajanov, Dimitar; Mishev, Kostadin (IEEE, 2017)
A concept guided by the ISO 37120 standard for city services and quality of life is suggested as unified framework for smart city dashboards. The slow (annual, quarterly, or monthly) ISO 37120 indicators are enhanced and complemented with more detailed and person-centric indicators that can further accelerate the transition toward smart cities. The architecture supports three tasks: acquire and manage data from heterogeneous sensors; process data originated from heterogeneous sources (sensors, OpenData, social data, blogs, news, and so on); and implement such collection and processing on the cloud. A prototype application based on the proposed architecture concept is developed for the city of Skopje, Macedonia. This article is part of a special issue on smart cities.